2022
DOI: 10.53097/jmv.10056
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical power in AVM-2 versus conventional ventilation modes in various ARDS lung models. Bench study

Abstract: Introduction Mechanical power has been linked to ventilator induced lung injury and mortality in acute respiratory distress syndrome (ARDS). Adaptive Ventilator Mode-2 is a closed-loop pressure-controlled mode with an optimal targeting scheme based on the inspiratory power equation that adjusts the respiratory rate and tidal volume to achieve a target minute ventilation. Conceptually, this mode should reduce the mechanical power delivered to the patients and thus reduce the incidence of ventilator induced lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…20 Similar findings in a bench study that showed that showed the AVM-2 mode delivered significantly less mechanical power than VCV, which in turn was less than PCV in various ARDS severity. 21 The impact of mechanical power is consistent and independent of the presence of ARDS and the use of neuromuscular blockers, and even with the maintenance of tidal volume and driving pressure at low values, it was associated with worse outcomes, which suggests that mechanical power adds information that go beyond just the tidal volume and driving pressure. 22 Regarding the comparison between survival and death outcomes, except for PEEP, Ve, PRresist and resistance, the mean values of all the other components showed significance in relation to the outcome in the isolated assessment.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…20 Similar findings in a bench study that showed that showed the AVM-2 mode delivered significantly less mechanical power than VCV, which in turn was less than PCV in various ARDS severity. 21 The impact of mechanical power is consistent and independent of the presence of ARDS and the use of neuromuscular blockers, and even with the maintenance of tidal volume and driving pressure at low values, it was associated with worse outcomes, which suggests that mechanical power adds information that go beyond just the tidal volume and driving pressure. 22 Regarding the comparison between survival and death outcomes, except for PEEP, Ve, PRresist and resistance, the mean values of all the other components showed significance in relation to the outcome in the isolated assessment.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, in order to recognize if the mechanical power is increased by iatrogenesis in the ventilation adjustments, or if it is increased by the severity of ARDS, or even if it is related to incurability by VILI, we would possibly have to somehow index the mechanical power with the compliance or elastance. 21 Theoretically, a well aerated lung with better compliance will require less mechanical power i.e. lower Power Compliance Index (higher Power Elastance Index), versus a non-aerated lung with poorer compliance will require higher mechanical power i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms our previous bench work where we found lower mechanical power, and PCI between AVM-2 compared to conventional VCV and PCV in an ARDS lung model with different severities. 13 As Marini and colleagues 18 suggested, normalizing or indexing the mechanical power to the compliance of the lung or the amount of aerated lung might be more meaningful than mechanical power alone, as it represents the amount of energy delivered to a specific injured unit. Coppola and colleagues 22 conducted a retrospective study in ARDS patients and found that the mechanical power alone did not correlate with mortality, however, mechanical power normalized to the compliance or to the amount of well-aerated tissue is independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant decrease in mechanical power, tidal volume, and inspiratory pressures. 13 In this study, we intended to analyze the differences between the established PCV and the innovative AVM-2 modes to measure disparities in mechanical power, including its key components: PEEP work, tidal work, elastic work, resistive work, inspiratory work, total work, tidal volume, tidal volume/IBW, and driving pressure. We hypothesized that AVM-2 would deliver less work (J) and mechanical power (J/min) compared to PCV, suggestive of greater lung protection.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive Ventilation Mode-2 (AVM-2) is a closed loop mode of ventilation with an optimal targeting scheme using the concept of mean inspiratory power (sum of the resistive and tidal power) that takes the VD into account in its algorithm for targeting the optimal VT and respiratory rate. 39,40 -Alveolar resistance…”
Section: -Alveolar Stressmentioning
confidence: 99%